2015
DOI: 10.1111/jfpp.12687
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Chemical Composition of Aerials Parts of Verbena minutiflora

Abstract: Verbena minutiflora (Verbenaceae) is popularly consumed as an infusion for the treatment of various diseases. However, so far there is no pharmacological or chemical validation to support its therapeutic applications. Therefore, the analysis of the chemical composition and pharmacological activities of V. minutiflora is crucial. In this study, extracts and infusions of the aerial parts of V. minutiflora (leaves, flowers and stems) were analyzed during four consecutive years. Extracts of leaves and flowers had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In the literature, it is described that plants tend to have higher concentrations of metals and organic compounds in their aerial parts, such as leaves (SOARES, et al, 2015). The CV samples, in addition to the leaves, also contained parts of the stem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, it is described that plants tend to have higher concentrations of metals and organic compounds in their aerial parts, such as leaves (SOARES, et al, 2015). The CV samples, in addition to the leaves, also contained parts of the stem.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the total levels of phenolic compounds, the Folin-Ciocalteau colorimetric method was used using an analytical curve (40.0 to 340 mg L -1 ) of gallic acid in methanol (SCHMIDT, et al, 2014;SOARES, et al, 2015).…”
Section: Quantification Of Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the quantification of the total content of the phenolic compounds, it was used the colorimetric method of Folin-Ciocalteau (Schmidt et al, 2014;Soares et al, 2015).…”
Section: Antioxidant Capacity: Total Phenolics and Total Flavonoidsmentioning
confidence: 99%
“…The Verbenaceae is popularly known as Gervão, Gervão-roxo, Rinchão, Gervão do campo, and Vassourinha de botão; and is frequently used as infusion (tea) in the treatment of various diseases (Schapoval et al, 1998). However, at present few studies have been found on chemical and pharmacological validation of this plant (Soares et al, 2016;Peloi, Bovo, Messias-Reason, & Perez, 2016).…”
Section: Introductionmentioning
confidence: 99%